Desenvolvimento de metodologia para determinação de talco em polpa celulósica por espectrofotometria de absorção atômica - Tatiane Rodrigues de Abreu (2015)
Talc or magnesium silicate is a mineral of natural occurring that has been widely used in the pulp and paper industries. It is commonly used as a filler additive in some types of papers and adsorbents of the pitch (sticky deposit formed in the machinery). However, the talc added in the process may remain in the system and depositing on the pulp fibers. This silicate may affect the contact between the fibers, leading to reduction in the strength of the paper, because of it, the presence of talc is considered a quality parameter, determining the final application of the paper. This way the aim of this study was to develop and validate a rapid and efficient analytical methodology to quantify the talc content in cellulosic pulp. The determination was performed using the magnesium content present in the talc. For this determination, initially, the pulp samples were subjected to digestion in a microwave oven and, later analysis by spectrometry of atomic absorption with flame. Four conditions of digestion were evaluated. For validation, we considered the linear parameters, matrix effects, detection limit, quantification limit, selectivity, precision and accuracy. The optimized methodology and validity was applied in real samples. Calibration curves presented determination coefficients greater than 0.999 and LQ of the curve was 0.002% of talc in pulp. The RSD for the precision were less than 8.0% and recovery experiments concerning the accuracy of the method were from 92.60% to 96.19% for the curve in the array. The methodology was fast, easy to perform, precise, accurate and sensitive in quantification of talc in cellulosic pulp and paper.